Phylogeographic structure of Heteroplexis (Asteraceae), an endangered endemic genus in the limestone karst regions of southern China - Zhu, Xianliang; Liang, Hui; Jiang, Haolong; Kang, Ming; Wei, Xiao; Deng, Lili; Shi, Yancai (Frontiers in Plant Science, 2022)
Though the karst regions in south and southwest China are plant diversity hotspots, our understanding of the phylogeography and evolutionary history of the plants there remains limited. In this study, species-level phylogeographic analysis of the endangered endemic genus Heteroplexis (Asteraceae) in the limestone karst regions of southern China was conducted using restriction site-associated DNA sequencing (RADseq). We found a clear phylogeographic structure among species, which was consistent with current species boundaries. The significant global and regional isolation by distance (IBD) signals among species indicate strong geographic isolation in the karst mountains, which may result in chronically restricted gene flow and increased genetic drift and differentiation. Furthermore, the phylogeographic structure of Heteroplexis suggested a southward migration since the last glacial period. Demographic analysis revealed the karst mountains as a refuge for Heteroplexis species. Finally, we detected significant historical gene flow between species. Significant historical gene flow and long-term stability of effective population size (Ne) together explain the high genome-wide genetic diversity among species. However, the recent collapse of Ne, widespread inbreeding within populations, and restricted contemporary gene flow suggest that Heteroplexis is probably facing a high risk of genetic diversity loss. Our results help to understand the evolutionary history of karst plants and guide conservation.